2004
DOI: 10.1023/b:neon.0000041887.51906.b7
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Radiosurgery for Pituitary Adenomas: A Review of the Literature

Abstract: Although surgical resection typically is the primary treatment modality, stereotactic radiosurgery offers safe and effective treatment for recurrent or residual pituitary adenomas. In rare instances, radiosurgery may be the best initial treatment for patients with pituitary adenomas. Refinements in the radiosurgical technique will likely lead to improved outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
95
2
6

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 91 publications
2
95
2
6
Order By: Relevance
“…Colin et al 7 reported no visual complications in 110 patients treated with 50.4 Gy in 1.8 Gy per fraction. Witt et al 9 and Laws et al 10 11 Twice daily fractionation of 1.2 Gy each is also reported in order to reduce the optic pathway complications. 5 Our study shows the visual complication rate of 5.3% and 10% more chances of developing visual complication for the conventional technique as compared to the SRT technique probably due to the possibility of hot spot on the chiasm and visual apparatus.…”
Section: Visualmentioning
confidence: 99%
“…Colin et al 7 reported no visual complications in 110 patients treated with 50.4 Gy in 1.8 Gy per fraction. Witt et al 9 and Laws et al 10 11 Twice daily fractionation of 1.2 Gy each is also reported in order to reduce the optic pathway complications. 5 Our study shows the visual complication rate of 5.3% and 10% more chances of developing visual complication for the conventional technique as compared to the SRT technique probably due to the possibility of hot spot on the chiasm and visual apparatus.…”
Section: Visualmentioning
confidence: 99%
“…Benign tumors of the CNS are candidates to perform RS 1 . It has emerged as a therapeutic option for clinically nonfunctioning pituitary adenomas (CNFPA), associated with effective control of tumor growth and few complications 1 .…”
Section: Radiosurgery (Rs) Is a Minimally Invasive Technique Suitablementioning
confidence: 99%
“…Benign tumors of the CNS are candidates to perform RS 1 . It has emerged as a therapeutic option for clinically nonfunctioning pituitary adenomas (CNFPA), associated with effective control of tumor growth and few complications 1 . About 30% of pituitary adenomas are classified as CNFPA, and patients with this tumor usually have clinical symptoms, such as headaches, visual loss, hypopituitarism and, less commonly, pituitary apoplexy 2 .…”
Section: Radiosurgery (Rs) Is a Minimally Invasive Technique Suitablementioning
confidence: 99%
See 2 more Smart Citations